Обер-прокурор Святійшого синоду Іван Іванович Меліссіно та його спроба реформування Російської православної церкви - Пархоменко, О. М. (Видавництво НДУ ім.М. В. Гоголя, 2017)
Стаття присвячена висвітленню життєвого шляху Івана Івано- вича Меліссіно та оцінці його діяльності на посаді обер-прокурора Святійшого синоду. Особлива увага приділена аналізу проекту реформування церковного життя, що був поданий Меліссіно на роз- гляд Синоду у підготовив наказу для делегата від духовенства до нової комісії, утвореної для зміни основного законодавства імперії. Аналіз пунктів реформи проводиться з точки зору відповідності церковним канонам та актуальності для тогочасних соціально- політичних реалій. Визначаються пункти, що в ході наступного історичного розвитку церкви були повністю, або частково реалі- зовані, ті, що не були реалізовані, але зберігають актуальність і ті, що не можуть бути реалізовані через невідповідність православ- ному віровченню.
The work is dedicated to the tenure of life and activities of Ivan Melissino, especially during the period of his excellence as Chief Procurator of the Holy synod of the Russian Orthodox Church. Ivan Melissino (171^-1795) is a representative of the ancient Byzantine aristocratic family. He served the Russian Empire and became the second director of the Moscow University. In 1763, Empress Catherine II appointed Ivan as the Chief Procurator of the Holy Synod to promote her reforms. Amongst his accomplishments, renewal of the suspended process of secularization of church lands was the first to his credit. In 1767, Melissino introduced to the Synod of the Church a 13-point draft reform. This project was not considered and Melissino was soon released. The article provides a brief analysis of each point in the project based on his point of view both in terms of compliance with the church canons and the relevance of contemporary church and socio-political realities. Some of the points were gradually implemented during the next historical development of the Church and those that were not implemented continued to remain relevant. Some of them could not be realized due to non-compliance with the Orthodox doctrine.
Keywords: Російська православна церква; церковні реформи Катерини II; просвітницькі ідеї; Russian Orthodox Church; Chief Procurator